Rapid NO conversion with an enhanced Sm+3-TiO2 photocatalyst - Alviz Meza, A.; Sierra González, X.; Martínez de la Cruz, Azael; Colina Marquez, J.A. (Elsevier, 2024)
Nitrogen oxides (NOx) are known for having a significant greenhouse effect and provoking several health issues. Because of that, it is necessary to find an effective manner to remove them from polluted air. In this study, samarium-doped titania was synthesized via sol-gel using two different synthesis routes and varying the calcination temperature and the Sm3+ content. The main difference between the two syntheses was the pH solution. The acidic pH favored the presence of the anatase crystalline phase, the most photoactive and interesting for photocatalytic applications. Furthermore, these catalysts were evaluated in a lab-scale UV photoreactor following the NO conversion via chemiluminescence, according to the ISO standard 22197–1. The Sm content positively affected the NO removal. The highest NO conversion was 92 %, with the doped titania obtained at a calcination temperature of 500 ◦C and with 0.5 % wt. of samarium. This result was congruent with the reported literature’s energy bandgap estimated (2.98 eV).